Exploration of the Use of Artificial Intelligence in Business Processing by KOL Marketing Agencies - Satria, Ryuki (International Journal Labs, 2025)
This study aims to examine the use of Lark's Artificial Intelligence (AI) platform in supporting business processes in Key Opinion Leader (KOL) marketing agencies, with a case study on Orbeat Digital Agency. The research method used is a qualitative approach with data collection techniques in the form of participatory observation, semi-structured interviews, and documentation. The results show that Lark plays a significant role in improving operational efficiency, strengthening team coordination, and facilitating real-time management of campaign projects. However, there are still obstacles such as the need for a stable internet connection and the process of adapting new users. This study recommends strengthening digital infrastructure and internal training to optimize the use of Lark.